Pengaruh Tingkat Pendidikan Dan Usia Terhadap Produktivitas Tenaga Kerja Diperkebunan Apel (Studi Kasus Pada Perkebunan Apel Kabupaten Pasuruan) - Ahmad Alan Ferry F; Nurhajati Nurhajati; M. Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractFrom this study, the following results were obtained: From this study it was concluded that both Education and Age had an effect on labor productivity in the Nongkojajar apple plantation. Education has an effect on labor productivity in the Nongkojajar apple plantation. Age has no effect on labor productivity in the Nongkojajar apple plantation. The level of education and age simultaneously have a positive and significant effect on labor productivity. This shows that their education level and age have a positive and significant effect on labor productivity. Keywords: Education, Age, Labor Productivity